The Role of Communication in Organizations: Understanding Verbal, Non-Verbal, and Written Aspects (Review of Management Literature) - Argarini, Fitri (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Communication plays a crucial role in organizations as it influences individual interactions and the achievement of organizational goals. Within organizations, communication occurs in three main forms: verbal, non-verbal, and written. Each form contributes to shaping perceptions, building understanding, and supporting accurate decision-making. However, misunderstandings often arise due to differences in individual or group perceptions, which can impact work effectiveness and relationships among organizational members. This study aims to explore the role of verbal, non-verbal, and written communication in fostering effective relationships within organizations. Using a qualitative method and literature review, this research provides an in-depth examination of communication phenomena in organizational settings. The findings indicate that clear and effective communication—whether verbal, non-verbal, or written—can enhance employee performance, facilitate information flow, and strengthen collaboration within organizations. Therefore, it is essential for organizations to understand and implement effective communication strategies to minimize potential misunderstandings and improve work effectiveness as well as the achievement of organizational goals.